Accumulation of positrons from a LINAC based source - Niang, Samuel; Charlton, M.; Choi, J. J.; Chung, M.; Clade, P.; Comini, P.; Crivelli, P.; Crepin, P-P; Dalkarov, Oleg; Debu, P.; Dodd, L.; Douillet, A.; et al. (Acta Physica Polonica A, 2020)
The GBAR experiment aims to measure the gravitational acceleration of antihydrogen H. It will use H + ions formed by the interaction of antiprotons with a dense positronium cloud, which will require about 1010 positrons to produce one H +. We present the first results on the positron accumulation, reaching 3:8±0:4×108 e+ collected in 560 s.
CRIS-Team Scopus Importer:2023-03-27